Dowry in Imam Malik's Fiqh: Implications and Relevance in the Context of Contemporary Society - Winario, Mohd; Harahap, Ahmad Rofi'i (Journal of Legal Sustainability, 2024)
This paper aims to examine Imam Malik's views on dowry and its implications in the context of contemporary society. The method used in this research is literature analysis of Imam Malik's Fiqh books, especially Al-Muwatta, as well as a study of ulama interpretations and other related literature. The research results show that Imam Malik emphasizes the importance of dowry as a form of respect and protection for women's rights in marriage. In the context of contemporary society, Imam Malik's views on dowry have great relevance. Dowry is not only a woman's right, but also a way to maintain justice and equality in marriage. By understanding Imam Malik's views on dowry, contemporary society can learn valuable lessons in maintaining Islamic values in the institution of marriage.